2018
DOI: 10.1080/10715762.2018.1542141
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible plasma and muscle protein oxidation and physical exercise

Abstract: The imbalance between the reactive oxygen (ROS) and nitrogen (RNS) species production and their handling by the antioxidant machinery (low molecular weight antioxidant molecules and antioxidant enzymes), also known as oxidative stress, is a condition caused by physiological and pathological processes. Moreover, oxidative stress may be due to an overproduction of free radicals during physical exercise. Excess of radical species leads to the modification of molecules, such as proteinsthe most susceptible to oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…These structural changes can lead to protein cross-linking, which modifies the physicochemical and biological properties of proteins, as well as decreasing their susceptibility to degradation [ 40 , 41 ]. Protein carbonylation is an irreversible process, which means that damaged molecules are not repaired, and if they are not degraded, they can strongly disrupt cellular metabolism [ 42 ]. It has been shown that as a result of oxidative modification of protein molecules, their surface hydrophobicity increases, which is a key signal for the proteolytic system to recognize the protein and initiate its degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These structural changes can lead to protein cross-linking, which modifies the physicochemical and biological properties of proteins, as well as decreasing their susceptibility to degradation [ 40 , 41 ]. Protein carbonylation is an irreversible process, which means that damaged molecules are not repaired, and if they are not degraded, they can strongly disrupt cellular metabolism [ 42 ]. It has been shown that as a result of oxidative modification of protein molecules, their surface hydrophobicity increases, which is a key signal for the proteolytic system to recognize the protein and initiate its degradation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS upregulate the expression of antioxidant enzymes leading to a stimulation of the antioxidant defense system. However, an increase in ROS production or a reduction in antioxidant capacity results in an imbalance and the redox state becoming pro-oxidant causes molecular damage [41]. Elite athletes have a very strong antioxidant defense system but a prolonged and strenuous exercise without an adequate rest period can lead to oxidative damage producing protein oxidation and developing muscle fatigue, injury and overreaching/overtraining with the impairment of sport performance.…”
Section: Redox Homeostasis and Oxidative Stress In Sportsmentioning
confidence: 99%
“…Even though the pathogenesis of psoriasis is not fully understood, it is accepted that reactive-oxygen species (ROS) and oxidative stress contribute to disease progression ( 34 ). The resulting protein carbonylation, which was detected in patients with psoriasis ( 35 ), is irreversible and requires defective proteins to be degraded in order not to disrupt cellular metabolism ( 36 ). Such proteins are degraded mainly by the proteasome ( 37 ), which is dysregulated in many diseases ( 38 ).…”
Section: Discussionmentioning
confidence: 99%